Advances in new antivirals for chronic hepatitis B. Issue 5 (5th March 2022) - Tang, Yanhua; Liang, Hongyan; Zeng, Ge; Shen, Sheng; Sun, Jian
Abstract : Abstract: Chronic hepatitis B virus (HBV) infection remains a global health burden. Timely and effective antiviral therapy is beneficial for patients with HBV infection. With existing antiviral drugs, including nucleos(t)ide analogs and interferon-alfa, patients can achieve viral suppression with improved prognosis. However, the rate of hepatitis B surface antigen loss is low. To achieve a functional cure and even complete cure in chronic hepatitis B patients, new antivirals need to be developed. In this review, we summarized the advantages and disadvantages of existing antiviral drugs and focused on new antivirals including direct-acting antiviral drugs and immunotherapeutic approaches.